Pengaruh Corporate Social Responsibility, Pengungkapan Emisi Karbon (GRI-305), dan Skor ESG terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Financials-Perbankan di BEI Periode 2020–2024 - Khairul Thaffan; Fanji Farman (Jurnal Riset Akuntansi, 2026)
This study aims to examine the effect of CSR disclosure, carbon emissions disclosure (GRI 305), and ESG scores on firm value in banking subsector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Specifically, the study tests the partial effects of each independent variable as well as their simultaneous effect on firm value, providing empirical evidence on the relevance of sustainability practices in value formation within the banking sector. A quantitative approach with an associative-causal design is employed using panel data. Secondary data are collected from companies’ financial statements, annual reports, and sustainability reports. The population comprises 46 listed banking firms, while purposive sampling yields 39 firms, resulting in 195 firm-year observations. Firm value is proxied by Price to Book Value (PBV), whereas CSR, carbon emissions (GRI 305), and ESG are measured using disclosure-based indices. The analysis includes descriptive statistics, assumption testing, and panel regression to evaluate the overall model (F-test), individual effects (t-test), and explanatory power (R²). The findings are expected to provide practical insights for managers, investors, and regulators to strengthen sustainability reporting quality and strategic initiatives that support higher firm value.